A Transiting Giant on a 7.7 yr Orbit Revealed by Transit Timing Variations in the TOI-201 System - Gracjan Maciejewski; Weronika Łoboda (The Astrophysical Journal Letters)
We report the detection and characterization of TOI-201 c, a long-period transiting companion to the warm Jupiter TOI-201 b. Its presence was first inferred from high-amplitude transit timing variations (TTVs) in TOI-201 b, pointing to a massive outer body on a $7.{7}_{-0.6}^{+1.0}$ yr eccentric orbit. This prediction was confirmed when Transiting Exoplanet Survey Satellite observed a transit of TOI-201 c, precisely constraining its orbital geometry. A joint fit to TTVs, transit photometry, and archival radial velocities yields a mass of $14.{2}_{-1.2}^{+1.0}$ M _Jup and an eccentricity of $0.64{3}_{-0.021}^{+0.009}$ . The mutual inclination between planets b and c is $2\mathop{.}\limits^{^° }{9}_{-4.4}^{+4.8}$ , indicating a nearly coplanar architecture. Long-term numerical integrations confirm dynamical stability over gigayear timescales and predict that transits of TOI-201 b will cease within a few thousand years. TOI-201 c ranks among the longest-period transiting planets with well-constrained properties. Its detection via TTVs, followed by a confirmed transit, represents a rare observational sequence and highlights the power of TTVs and photometric monitoring to uncover distant companions. The TOI-201 system offers a valuable laboratory for testing models of giant planet formation, migration, and secular evolution in multiplanet systems.